Optimising Science Literacy and Learning Activity through Audio-Visual Media in Elementary School Science Learning - Ni Kadek Dwi Pramita; I Wayan Kertih; I Wayan Widiana (International Journal of Language and Literature, 2025)
This research is motivated by the low scientific literacy skills and low learning activity of elementary school students in science learning, which is still dominated by conventional learning models, resulting in students being less actively involved. This study aims to analyse the effect of applying the Project-Based Learning model, supported by audiovisual media, on the scientific literacy skills and learning activity of fifth-grade elementary school students in science subjects. This study uses a quantitative approach, a quasi-experimental design, and a nonequivalent control group design. The study subjects were fifth-grade elementary school students, divided into an experimental and a control group. Data collection was conducted through essay tests and questionnaires. The data obtained were analysed using descriptive statistical analysis and inferential statistics. The study found significant differences in scientific literacy skills and student learning activities between the group taught using the Project-Based Learning model assisted by audiovisual media and the group taught using conventional learning models. Students in the experimental group obtained higher average scores in scientific literacy skills and learning activeness than the control group. These findings indicate that the application of the Project-Based Learning model, supported by audiovisual media, is effective in improving students' scientific literacy skills and learning activities.